ابن أبي طي المؤرخ الموسوعي (Journal of the College of Education for Women, 2019)
Our humble study for the historian (Ibn Abi Tai) shows us ideological value inhistory and his capability of sciences, religious and jurisprudential knowledge, readings,syntax and poetries. He is encyclopedic historian due to his cognizance on kinds ofsciences and humanitarian knowledge; although some of his age historians accused hismethods and ability of writing and recording. However, when we look closely at hiscorpuses and classifiers; we can recognize the capability of this historian to interaction inwhat he witnessed in his age in fields of science and intellect; he left his classifiers andheritage that overflow the Arabian library in numerous specializations that lately becamean important recourses for students of humanitarian science & knowledge.